Conceptualizing sustainability in the real estate development process - Upuli Perera; Collins Adjei Mensah (Center for Science and Technology, IAIN Surakarta, 2019)
Operationalizing sustainability within the real estate development is a challenge as such development process is complex, multidisciplinary in nature and involves multiple agencies. The paper, therefore, aims at strengthening the conceptualization of sustainability within the real estate development process (REDP) to address this challenge effectively. Adopting the systematic review, 127 publications focused on sustainability and REDP were appraised. Focusing on the institutionalist viewpoints, sustainability was found to be a problem driven notion which is socially constructed. Therefore, it requires to be viewed within the larger picture of agency, structure and power in the context of economic, social and environmental uncertainties. These are found to be applied in the same way in the contemporary REDP literature too. On account of this, the paper suggests, conceptualizing sustainability within REDP needs the latter to take into account the agency dynamics of actors in the development process such as agency motivation (values) to offer a meaningful operationalization of the concept. In other words, this paper calls for significant stakeholder participation in the REDP which allows significant levels of economic, social and environmental values of actors to be brought forward to build consensus to determine as to what is sustainability within it.